EFFECTS OF HUMAN ACTIVITIES ON QUALITY OF WATER AT SELECTED POINTS OF RIVER RUPINGAZI IN EMBU COUNTY, KENYA - Bonareri, Somoni Prisca; Kitur, Dr. Esther; Koske, Dr. James (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Quality of water in rivers and lakes depends on physical, chemical and biological properties. Points in inland water resources in Kenya are under pressure of pollution from agrochemicals, municipal and other domestic wastes variably affecting water quality. This study assessed the effects of human activities on water quality of river Rupingazi and its major tributaries. The parameters studied included: temperature, pH, EC, DO, TSS, TDS, turbidity, phosphates, nitrates and nitrites. Laboratory and field data was statistically analysed (p<0.05) using one way  ANOVA, t-Test and regression. The results obtained showed significant seasonal variation between some parameters for wet and dry seasons. Temperature and pH were significantly higher in dry season recording 22.97±0.2 0C and 8.16±0.04 respectively (n=36, p<0.05). Turbidity, DO, TSS and nitrates were all significantly higher in wet season. Recorded results were Turbidity 98.59±13.34 NTU; DO 6.64±0.31 mg/L; TSS 103.33±12.43 mg/L; Nitrates 12.16±1.88 mg/L (n=36, p< 0.05). There was no noted significant variation in EC and TDS for both seasons (n=36,p>0.05).